Contact Load and Elastohydrodynamic Lubrication Analysis of Eccentric Bearings in RV Reducer Considering the Effects of Roller Profile Modification - Xinyue Zhang; Gang Wang; Daqi Wu; Jian Guan; Wenjie Chen (Lubricants)
The mechanical and tribological behavior of eccentric bearings is crucial for the performance of a RV reducer. By combining the finite element model (FEM) and the elastohydrodynamic lubrication (EHL) method, a comprehensive model for the cylindrical roller bearings applied in the RV reducer is developed in this study. During the modeling phase, FEM is utilized to determine the bearing load, taking into account the structural flexibility. The FEM result demonstrates that a 15% increase in the maximum bearing’s load is detected by the FEM compared to the analytical model. After the simulations, the effects of the roller profile modification, the bearing load and the rolling speed on the bearing performance are revealed. The numerical results indicate that the combined generatrix shape roller results in weaker edge effects and stress concentration compared with that of the straight generatrix shape roller and the arc generatrix shape roller. The optimal values of modification length and modification quantity under various load and rolling speed conditions are provided. Furthermore, durability tests on RV reducers equipped with the three types of rollers were conducted. Experimental outcomes demonstrate that the combined generatrix shape roller significantly improves the reliability and fatigue life of the RV reducer, corroborating the numerical analyses.